2011
DOI: 10.1258/td.2011.110121
|View full text |Cite
|
Sign up to set email alerts
|

Clubfoot in Malawi: treatment-seeking behaviour

Abstract: We explore the treatment-seeking behaviour of guardians of patients undergoing treatment for clubfoot at clinics run by the Malawi National Clubfoot Programme (MNCP). Core data was collected and analysed using qualitative methodologies of critical medical anthropology. Sixty detailed case studies were completed, each based on an extended open-ended interview with patient guardians. Two positive drivers in seeking treatment for clubfoot were identified: a desire to correct the impairment; and a direct instructi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 4 publications
0
13
0
1
Order By: Relevance
“…Other studies have also shown that transport expenses are a major barrier to follow-up in Malawi (Yu et al 2007, Bedford et al 2011). The present study lends some support to the assumption that patients who do not have problems do not return for review, at least in Malawi, as no infections were found in the 29 patients who did not return for follow-up of their own accord.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Other studies have also shown that transport expenses are a major barrier to follow-up in Malawi (Yu et al 2007, Bedford et al 2011). The present study lends some support to the assumption that patients who do not have problems do not return for review, at least in Malawi, as no infections were found in the 29 patients who did not return for follow-up of their own accord.…”
Section: Discussionmentioning
confidence: 98%
“…Surgeons working in low-income countries (LICs) often have the impression that patients do not return for follow-up if they have no complaints, but that they do return if they have a serious problem. A frequent reason given by patients for not returning for review in Malawi is the cost of transport (Yu et al 2007, Bedford et al 2011). In an earlier study of the SIGN Online Surgical Database (SOSD), we found that a statistical model supported the notion that patients who do not return for follow-up after trauma surgery in LMICs have few infections (Young et al 2011), but prospective studies with better follow-up rates are needed to shed more light on this.…”
mentioning
confidence: 99%
“…A priority in planning for and providing appropriate and accessible services is the identification of barriers to care and strategies to overcome them [4]. There now exists a wealth of literature focusing on care-seeking behaviour and associated barriers concerning different disabilities in a range of settings [see for example [5][6][7][8][9]. Although local context shapes the presentation of barriers faced by people with disabilities (as it shapes perceptions of disability itself [10]), common themes are evident.…”
Section: Introductionmentioning
confidence: 99%
“…Em um estudo realizado em Malawi e Uganda, houve uma série de considerações errôneas sobre as causas do pé torto e muitas vezes as pessoas não procuravam tratamento porque não tinham conhecimento sobre a sua disponibilidade e não consideravam o pé torto como uma condição corrigível (16,17) . Em estudo realizado no Paquistão, foi encontrado que muitas vezes a culpa da doença era atribuida às mães, o que pode levar à estigmatização das famí-lias de crianças com pé torto e gerar um impacto negativo sobre as mães dessas crianças (18) .…”
Section: O Esclarecimentounclassified